Compreender a vida, fundamentar a história: a crítica da razão histórica em Wilhelm Dilthey (1833 1911) - Edmar Luis da Silva (2006)
This thesis intends to discuss the nature of historical knowledge in the work of the German historian and philosopher Wilhelm Dilthey (1833 1911). For this matter, we discuss his main works that deal with this subject, starting from his biggest production: the Introduction to the Human Sciences. We show that Dilthey emphasizes the peculiarities of this knowledge in face of the group called particular sciences, evenhe considers the history as a science. We also show the application of his methods e and the vivacity of his work to search the historiographical production in his time and also his contributions to the theoretical debates nowadays.